2013
DOI: 10.1111/1471-0528.12223
|View full text |Cite
|
Sign up to set email alerts
|

High‐grade vaginal intraepithelial neoplasia: can we be selective about who we treat?

Abstract: Objective To determine the role of conservative management in high-grade vaginal intraepithelial neoplasia (HG VaIN).Design Retrospective observational study.Setting Northern Gynaecological Oncology Centre, Gateshead, UK.Population A total of 100 women with histologically-proven HG VaIN.Methods Review of patient records from 1995 to 2011.Main outcome measures Rates of progression to cancer, treatment remission, and disease recurrence, particularly posttreatment when vaginoscopy is normal but cytology is abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
2
33
1
2
Order By: Relevance
“…In this study, 6 % of the included women had or developed vaginal cancer, which is in the range of other reports [8][9][10]. All of these cases were HR-HPV positive, all primarily had VAIN grade 3.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this study, 6 % of the included women had or developed vaginal cancer, which is in the range of other reports [8][9][10]. All of these cases were HR-HPV positive, all primarily had VAIN grade 3.…”
Section: Discussionsupporting
confidence: 66%
“…This may be the case because of a very liberal definition of relapse in this study (abnormal cytology, suspicious colposcopy). This definition was used as abnormal cytology after treatment is often a sign for VAIN recurrence [10]. Other studies only considered histologically confirmed VAIN as relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma of the vagina can be preceded by vaginal intraepithelial neoplasia [VAIN], but the true malignant potential of VAIN is still unknown [6,[17][18][19]. VAIN has been sometimes detected in women with prior radiotherapy for gynecological malignancies [20].…”
Section: Epidemiology Risk Factors and Natural Historymentioning
confidence: 99%
“…Although the overall risk of invasive progression is only approximately 3% [10], physicians need to be mindful of underestimating larger lesions with malignant potential. Additional factors to consider when selecting the appropriate treatment for women with VaIN include prior hysterectomy, prior radiation therapy, age, sexual activity, comorbidities and vaginal anatomy [11].…”
Section: Introductionmentioning
confidence: 99%